Risk factors of bloodstream infection in erythroderma from atopic dermatitis, psoriasis, and drug reactions: a retrospective observational cohort study - Qian Liufu; Lulu Niu; Shimin He; Xuejiao Zhang; Mukai Chen (PeerJ, 2024)
Background Atopic dermatitis (AD), psoriasis, and drug reactions associated with erythroderma are frequently complicated by infections. However, bloodstream infection (BSI) have received less research attention. Objectives This study aimed to investigate the clinical characteristics and risk factors associated with BSI in patients with erythroderma. Methods A retrospective analysis was conducted on 141 erythroderma cases. Eleven cases were identified as having BSI. Clinical records of both BSI and non-BSI groups were reviewed and compared. Results BSI was diagnosed in 7.80% (11/141) of erythroderma cases, with a breakdown of 7.14% in AD, 2.00% in psoriasis, and 17.14% in drug reactions. Notably, all positive skin cultures (7/7) showed bacterial isolates concordant with blood cultures. Univariate logistic regression analysis revealed several significant associations with BSI, including temperature (≤36.0 or ≥38.5 °C; odds ratio (OR) = 28.06; p < 0.001), chilling (OR = 22.10; p < 0.001), kidney disease (OR = 14.64; p < 0.001), etiology of drug reactions (OR = 4.18; p = 0.03), albumin (ALB) (OR = 0.86; p < 0.01), C-reaction protein (CRP) (OR = 1.01; p = 0.02), interleukin 6 (IL-6) (OR = 1.02; p = 0.02), and procalcitonin (PCT) (OR = 1.07; p = 0.03). Receiver operating characteristic (ROC) curves demonstrated significant associations with ALB (p < 0.001; the area under curve (AUC) = 0.80), PCT (p = 0.009; AUC = 0.74), and CRP (p = 0.02; AUC = 0.71). Conclusions Increased awareness of BSI risk is essential in erythroderma management. Patients with specific risk factors, such as abnormal body temperature (≤36.0 or ≥38.5 °C), chilling sensations, kidney disease, a history of drug reactions, elevated CRP (≥32 mg/L), elevated PCT (≥1.00 ng/ml), and low albumin (≤31.0 g/L), require close monitoring for BSI development.